Alternative Decomposition Based Approaches for Assigning Dusjunctive Tasks - Haddadi, Salim; Slimani, Omar (Algorithmic Operations Research, 2007)
We consider a special linear assignment problem where some tasks are grouped, and in each group the tasks are disjunctive (in the sense that at most one of them could be performed). We show this problem NP-hard. Then we present and compare two alternative decomposition based algorithms on randomly generated instances.